"A Stain Remains". (June 2023) - ,
This community of 12 artists and writers had been brought together through the U.K.-based "Turps Banana" course program for painters by painters. They decided to write collaboratively about their experiences as painters, and of everyday life, at a time of global crisis (while they were writing, and painting, the world was experiencing a pandemic and Russia invaded Ukraine). They met together via "zoom" and read their words out loud, and then wrote into the space they had created. They repeated this process several times and then took turns in editing and collating the text.